Au nanoparticles and AuPVA Nano composites: Synthesis and characterization - Muslim laftah sabaar tami; Hassanein Ali Kazem Ali; Muqtada Arkan Karim Shaalan; Mohammed Riyadh Saadi Salih; Manaf Moayad Ahmed Dhiab (Genius Journals, 2024)
This research aims to prepare a nanocolloidal solution of gold and gold capped with PVA by chemical reduction method by sodium tri-citrate as a reducing agent and using gold chloride as a source of gold ions in aqueous solution at low temperatures (room temperature). The prepared solution was diagnosed by scanning electron microscope as well as the X-RayDiffraction. The results showed that the shape of the prepared particles is spherical with diameters close to 10 nanometers and with good scattering
Keywords: Synthesis; characterization; Au-PVA